2016
DOI: 10.1103/physreve.94.012605
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hydrogen bonds and temperature on dielectric properties

Abstract: Dielectric properties have been evaluated by means of Molecular Dynamics simulations on two model systems made up by dipolar molecules. One of them mimics methanol, whereas the other differs from the former only in the ability of forming hydrogen bonds. Static dielectric properties such as permittivity and the Kirkwood factor have been evaluated, and results have been analyzed by considering the distribution of relative orientations between molecular dipoles. Dipole moment time correlation functions have also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…† We have plotted E a,X as a function of −TDDS ‡ for each water model in Fig. 4D-F and tted these data to eqn (13). While the observed correlations are strong (R 2 between 0.842 and 0.887), they are weaker than that found for the enthalpic correlations.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…† We have plotted E a,X as a function of −TDDS ‡ for each water model in Fig. 4D-F and tted these data to eqn (13). While the observed correlations are strong (R 2 between 0.842 and 0.887), they are weaker than that found for the enthalpic correlations.…”
Section: Discussionmentioning
confidence: 83%
“…The ability of this network to quickly exchange these H-bonds is responsible for many of the noteworthy features of the neat liquid. [1][2][3][4] Under ambient conditions, H-bond exchanges play a critical role in most dynamical processes including diffusion, 5 reorientation, 6,7 viscosity, [8][9][10][11] dielectric relaxation, 12,13 structural rearrangements, 14,15 and chemical reactions. [16][17][18] Given that these exchanges play such a ubiquitous role, it is not surprising that they have received signicant attention.…”
Section: Introductionmentioning
confidence: 99%
“…The Debye rotational diffusion model [8] describes reasonably well the dynamics of non-associated liquids by considering that their molecules perform rotational Brownian motions [9]. It has been previously shown that methanol is a non-Debye fluid at room temperature [10], but its deviations from the Debye model for reorientation characteristic times are smaller than those obtained for water [11]. The extended jump model has proven to be successful in the analysis of molecular reorientation in hydrogen bonded liquids.…”
Section: Introductionmentioning
confidence: 99%